The genetic landscape on manifolds from human genes. (1st January 2014) - Cheng, Wei-Chen
The high throughput sequencing technology generates large amount of data and the computational methods therefore play important roles in bioinformatics research. This paper reports the findings from the result of analysing human genetic information by three manifold learning algorithms and two clustering methods. We target the genes that relate to human intelligence, selecting 38 of them, and marking them on the visualisation results.